Correlation analysis of MRD positivity in patients with completely resected stage I-IIIA non-small cell lung cancer: a cohort study - Dong, Daling; Zhang, Shixin; Jiang, Bin; Wei, Wei; Wang, Chao; Yang, Qian; Yan, Tingzhi; Chen, Min; Zheng, Liken; Shao, Weikang; Xiong, Gang (Frontiers in Oncology, 2023)
The primary objective of this study is to thoroughly investigate the intricate correlation between postoperative molecular residual disease (MRD) status in individuals diagnosed with stage I-IIIA non-small cell lung cancer (NSCLC) and clinicopathological features, gene mutations, the tumour immune microenvironment and treatment effects.The retrospective collection and analysis were carried out on the clinical data of ninety individuals diagnosed with stage I-IIIA NSCLC who underwent radical resection of lung cancer at our medical facility between January 2021 and March 2022. The comprehensive investigation encompassed an evaluation of multiple aspects including the MRD status, demographic information, clinicopathological characteristics, results from genetic testing, the tumor immune microenvironment, and treatment effects.Results: No significant associations were observed between postoperative MRD status and variables such as gender, age, smoking history, pathological type, and gene mutations. However, a statistically significant correlation was found between MRD positivity and T (tumor diameter > 3 cm) as well as N (lymph node metastasis) stages (p values of 0.004 and 0.003, respectively). It was observed that higher proportions of micropapillary and solid pathological subtypes within lung adenocarcinoma were associated with increased rates of MRD-positivity after surgery (p = 0.007;0.005). MRD positivity demonstrated a correlation with the presence of vascular invasion (p = 0.0002). For the expression of programmed cell death ligand 1 (PD-L1), tumour positive score (TPS) ≥ 1% and combined positive score (CPS) ≥ 5 were correlated with postoperative MRD status (p value distribution was 0.0391 and 0.0153). In terms of ctDNA elimination, among patients identified as having postoperative MRD and lacking gene mutations, postoperative adjuvant targeted therapy demonstrated superiority over chemotherapy (p = 0.027).Postoperative ctDNA-MRD status in NSCLC patients exhibits correlations with the size of the primary tumor, lymph node metastasis, pathological subtype of lung adenocarcinoma, presence of vascular invasion, as well as TPS and CPS values for PD-L1 expression; in postoperative patients with MRD, the effectiveness of adjuvant EGFR-TKI targeted therapy exceeds that of chemotherapy, as evidenced by the elimination of ctDNA.